Y RNA and Y RNA-derived ysRNA associations with viral pathogens - Olliff, Nathaniel S.; Mabien, Alexandria A.; Cole, Grayson M.; Borchert, Glen M. (Frontiers in RNA Research, 2025)
Y RNAs are a poorly-studied class of small non-coding RNAs (sncRNAs) which have previously been implicated in the pathogenesis of different human diseases, including cardiac and autoimmune conditions, as well as certain cancers. In recent years, however, multiple studies have reported correlations between Y RNA expressions and disease outcomes in viral infections (e.g., IAV, HIV, HPV, and SARS-CoV-2) as well as potential mechanistic roles that Y RNAs may play in host anti-viral defense. These studies suggest that Y RNAs may be associated with upregulation of viral defense proteins as well as altered cell-cell communication during viral infections. In this review, current literature detailing Y RNA effects on human viral infection will be summarized and future directions in the study of these relationships discussed.